2016
DOI: 10.18006/2016.4(2).201.209
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis and callus proliferation in Picrorhiza kurroa Royle ex. Benth

Abstract: Picrorhiza kurroa Royle ex. Benth is an endangered and important medicinal plant of alpine Himalayas. Developing an efficient protocol for its mass multiplication is essential to meet the requirements of pharmaceutical industries and also in conservation of this plant under its natural habitat. Present study was undertaken to develop a protocol for in vitro mass multiplication of P. kurroa. Result of study revealed that highest frequency of shoot regeneration was achieved on Murashige and Skoog's basal medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…These results are in accordance with Salvia officinalis L. (Tawfik and Mohamed 2007) and Picrorhiza kurroa Royle ex Benth. (Mahajan et al 2016) as nodal parts of plants possess more totipotency for culturing than leaves and inter nodes (Balilashaki et al 2015). However, a limited callogenic ability was also observed in leaves which is similar to reports of O. basilicum (Gopi and Ponmurugan 2006), O. sanctum (Lim et al 2009), Mentha piperita L. (Sujana and Naidu 2011) and broccoli leaves (Hossain et al 2016).…”
Section: Indirect Regenerationsupporting
confidence: 79%
“…These results are in accordance with Salvia officinalis L. (Tawfik and Mohamed 2007) and Picrorhiza kurroa Royle ex Benth. (Mahajan et al 2016) as nodal parts of plants possess more totipotency for culturing than leaves and inter nodes (Balilashaki et al 2015). However, a limited callogenic ability was also observed in leaves which is similar to reports of O. basilicum (Gopi and Ponmurugan 2006), O. sanctum (Lim et al 2009), Mentha piperita L. (Sujana and Naidu 2011) and broccoli leaves (Hossain et al 2016).…”
Section: Indirect Regenerationsupporting
confidence: 79%
“…It is a well-established herbal medicine for many ailments, ranging from dyspepsia to hepatitis [ 6 ]. Traditional and modern medicine have used bitter extracts from the dried rhizomes of this plant as a purgative, brain tonic, stomachic, and antiperiodic to treat dyspepsia [ 7 , 8 , 9 ]. Many traditional herbs are known for their cooling, heating, or neutral properties.…”
Section: Introductionmentioning
confidence: 99%
“…No major adverse effects have been reported for this plant. The diverse pharmacological activities of P. kurroa , a medicinally significant endangered plant, have led researchers to develop practical techniques for its in vitro mass multiplication [ 7 , 8 , 9 ]. The International Union for Conservation of Nature (IUCN) reported that this species should be protected under the rare endangered species (RET) category.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in ayurvedic system of medicine to treat the disorders of liver and upper respiratory tract, jaundice, fever, chronic diarrhea and scorpion sting (Krishnamurthy 1969;Vaidya et al 1996). The species shows hepato-protective, stomachic, anti-inflammatory, anti-tumor, immuno-modulatory, hypolipidemic, hypoglycemic and antispasmodic bioactivities (Tiwari et al 2012;Bhattacharjee et al 2013;Sultan et al 2016;Mahajan et al 2016). The pharmacological properties of P. kurroa are attributed to the presence of various monoterpene-derived Iridoide glycosides known as picrosides that include picroside-I, and picroside-II, metabolites picrosides III, IV and V and other compounds.…”
Section: Introductionmentioning
confidence: 99%